VA physicians intent to leave and correlations to drivers of burnout: a cross-sectional study - Robert C. Oh; David C. Mohr; Tamara M. Schult (BMC Health Services Research)
Abstract Background Physician well-being and workforce retention within the healthcare system is of critical importance. Understanding physicians’ intent to leave the organization will inform efforts on optimizing the physician workforce. In this study, we examine the association of burnout and specific drivers of burnout on turnover intentions. Methods The study was a cross-sectional design using data collected from an organization-wide workforce survey. The sample included 16,363 respondents from the Veterans Health Administration (VA). A multinomial model was run to compare physicians indicating turnover intent because they were: a.) changing internal jobs; b.) leaving the organization for another job; or c.) retiring, against physicians indicating they had no plans to turnover. Explanatory variables in the model included burnout, drivers of burnout, and demographics. We also asked about the primary reason behind turnover intent. Results Most physicians responding to the survey (n = 13,083, 80%) indicated they would stay within their current job, while 5.8% indicated they would look for another VA job, 5% indicated planning to retire, and 9.3% said they would leave the VA workforce altogether. Burnout and less favorable senior leadership perceptions were associated with greater odds of turnover intent specific to finding another VA job, leaving VA, or retire. Experiencing discrimination was related to turnover intent for another VA job and leaving VA, while satisfaction with workload and recognition were related to lower odds of finding another VA job or leaving VA. Culture of well-being was associated with lower odds of leaving VA. Conclusions The study highlights how burnout is associated with turnover intentions with physicians have differing rationales for leaving. Several drivers of burnout were related to turnover intentions for both finding another VA job and leaving VA altogether. Efforts to improve workforce well-being and drivers of burnout may help address the different rationales physicians may have for considering leaving.